Surviving as a Widow in 19th-century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
This paper is a preliminary attempt to examine demographic and economic aspects of widowhood in 19th-century Montreal and the ways working-class widows in particular could survive. Although men and women lost spouses in roughly equal proportions, widows remarried much less frequently than widowers. In the reconstruction of their family economy that followed the loss of the main wage earner, some of these women sought work themselves, mostly in the sewing trades or as domestics or washerwomen. A few had already been involved in small shops, and some used their dower, inheritance, or insurance policies to set up a shop, a saloon, or a boarding-house. Children were the most valuable asset of a widow, and they were more likely to work and to stay at home through their teens and twenties than in father-headed families. Additional strategies, including sharing housing with other families, raising animals, or trading on the streets, were drawn upon; they established an economy of makeshift arrangements that characterized the world of many working-class widows.